ACE2/Ang-(1–7)/Mas axis stimulates vascular repair-relevant functions of CD34(+) cells - Singh, Neha (Am J Physiol Heart Circ Physiol, 2015)
CD34(+) stem/progenitor cells have been identified as a promising cell population for the autologous cell-based therapies in patients with cardiovascular disease. The counter-regulatory axes of renin angiotensin system, angiotensin converting enzyme (ACE)/Ang II/angiotensin type 1 (AT(1)) receptor and ACE2/Ang-(1–7)/Mas receptor, play an important role in the cardiovascular repair. This study evaluated the expression and vascular repair-relevant functions of these two pathways in human CD34(+) cells. CD34(+) cells were isolated from peripheral blood mononuclear cells (MNCs), obtained from healthy volunteers. Expression of ACE, ACE2, AT(1), and angiotensin type 2 and Mas receptors were determined. Effects of Ang II, Ang-(1–7), Norleu(3)-Ang-(1–7), and ACE2 activators, xanthenone (XNT) and diminazene aceturate (DIZE) on proliferation, migration, and adhesion of CD34(+) cells were evaluated. ACE2 and Mas were relatively highly expressed in CD34(+) cells compared with MNCs. Ang-(1–7) or its analog, Norleu(3)-Ang-(1–7), stimulated proliferation of CD34(+) cells that was associated with decrease in phosphatase and tensin homologue deleted on chromosome 10 levels and was inhibited by triciribin, an AKT inhibitor. Migration of CD34(+) cells was enhanced by Ang-(1–7) or Norleu(3)-Ang-(1–7) that was decreased by a Rho-kinase inhibitor, Y-27632. In the presence of Ang II, XNT or DIZE enhanced proliferation and migration that were blocked by DX-600, an ACE2 inhibitor. Treatment of MNCs with Ang II, before the isolation of CD34(+) cells, attenuated the proliferation and migration to stromal derived factor-1α. This attenuation was reversed by apocynin, an NADPH oxidase inhibitor. Adhesion of MNCs or CD34(+) cells to fibronectin was enhanced by Ang II and was unaffected by Ang-(1–7). This study suggests that ACE2/Ang-(1–7)/Mas pathway stimulates functions of CD34(+) cells that are cardiovascular protective, whereas Ang II attenuates these functions by acting on MNCs. These findings imply that activation of ACE2/Ang-(1–7)/Mas axis is a promising approach for enhancing reparative outcomes of cell-based therapies.